Soil carbon stocks cultivated with coffee in the brazilian savana: Effect of cultivation time and use of organic compost - Belizário, Maísa Honório; Ferrão, Gregori da Encarnação; Cerri, Carlos Clemente; Siqueira Neto, Marcos (Coffee Science - ISSN 1984-3909, 2018)
Land-use change (LUC) is one of the main responsible for the loss of soil organic matter (SOM) in the form of CO2 to atmosphere. The aims of the present study were i) evaluate soil C stocks due to coffee cultivation time after LUC and ii) evaluate the use of the organic compost from the by-product of bean processing as a source of SOM. The study was performed in dystrophic red latosol in the municipality of Patrocínio, MG, Brazil. Two evaluations were performed; i) three coffee (Coffea arabica L. var. Icatú Vermelho) growing areas with different implantation times (8, 15 and 37 years) in relation to Cerrado stricto sensu (reference); and ii) area cultivated with coffee ( C. arabica var. Bourbon Vermelho) that received organic compost for four years. Soil was sampled in layers 0-5, 5-10 and 10-20 cm. In the first study, the C stock (0-20 cm) was higher under native vegetation (67 Mg C ha-1) in relation to the coffee growing (63 Mg C ha-1), however, did not differ significantly and showed subtle loss rates of 0.12; 0.06 and 0.02 Mg C ha-1 year-1 for 8, 15 and 37 years, respectively. In the second study, the organic compost applied to the soil increased the C stock (0-20 cm) to 4.6 Mg C ha-1 and showed an accumulation rate of 1.15 Mg C ha-1 year-1. Thus, it is concluded that C stocks is reduced in the soil due to LUC, however, the application of organic compost increased the supply of organic material, favoring the maintenance and even increasing the stock in the soil.